Lord Brocktree - Jacques, Brian; Fangorn (New York : Philomel Books, 2000)
The mountain of Salamandastron needs the help of Brocktree the Badger Lord when evil comes in the form of the Blue Hordes of Ungatt Trunn, the Earth Shaker.
Booklist.
School Library Journal.
Wilson's Junior High School.
6.3.
6.3
5-8
Keywords: Animals -- Fiction; Badgers -- Fiction; Fantasy; Animals -- Fiction; Badgers -- Fiction; Fantastic fiction